Performances of composite genotype resulting from crossingbetween local sumatera and hair sheep under confinement condition - Subandriyo .; Bambang Setiadi; Eko Handiwirawan; Agus Suparyanto (Indonesian Center for Animal Research and Development (ICARD), 2000)
Under semi-intensive conditions, the composite genotype (K) (25% Barbados Blackbelly; BB, 25% St. Croix; SC, 50% Sumatra Thin Tail; DETS) showed relatively have similar weaning weight as compared to other contemporary crossbred, therefore under intensive conditions (confined), they are expected to have better performances. The objective of the study are to find performances of the second generation composite genotype lambs and the first generation performances of the ewes, as well as several genetics parameters under intensive conditions, and compared to the Barbados Blackbelly Cross (BC) as contemporary crossbred. The growth of pre- and post-weaning of BB crossbred (BC) and the second generation of composite genotype (K-F2) are relatively the same. Growth curve using Von Bertalanffy model with the equation of Wt (t) = A*(1-B*e**(- K*t)), show that the equation for BC is Wt (t) = 26.8(1-0.92e**(-0.01t) and for K-F2 is Wt(t) = 26.1(1-0.92e**(-0.01t). This equation indicate that the growth of BC and K-F2 is not significantly different. The BC and K-F2 genotype reach maturity at the weight of 26.8 and 26.1 kg, respectively, and both with rate of reaching maturity of 0.01. Mating weight and weight at lambing of those two genotypes are around 29 - 30 kg dan 31 kg, respectively. The mean of litter size of BC and K-F1 are 1.52 and 1.48, respectively or around 1.5. The average litter size at weaning are 1.39 and 1.34, respectively for BC and K-F1. This means that pre-weaning mortality are around 5.37 and 9.76%, respectively for BC and K-F1. The lambing interval of BC and K-F1 are 211 and 223 days, or 0.58 and 0.61 year, respectively. Therefore the reproductive rate (RR) of the respective genotype are 1.39/0.58 = 2.39 and 1.34/0.61 = 2.19, respectively. The average of litter weight at weaning (LWW) of BC x BC, SC crossbred (HC) x BC and K-F1 x K-F1 are 11.62, 12.60 and 11.83 kg, respectively. Therefore based on the ewe genotype the LWW of BC and K-F1 are 11.74 and 11.83 kg, respectively. Flock productivity (FP) for those two genotypes per year are 20.24 and 19.39 kg, respectively for BC and K-F1. Dam productivity index (DPI) that calculated as /ewe weight for those two genotypes are 0.67 and 0.66, respectively for BC and K-F1. Meanwhile, the flock efficiency index (FEI) that calculated as FEI = FP/ewe weight0.75 for the respective genotypes are 1.57 and 1.54 for BC and K-F1. The estimates of repeatability of litter weight at weaning show relatively low value (0,092), therefore the estimate of MPPA (Most Probable Producing Ability) for predicting the future productivity is relatively the same. The estimate of MPPA for litter weight at weaning (LWW) for the respective genotype are 11.79 and 11.81 kg, respectively for BC and K-F1. Results of the study show that performances of composite genotypes (F) and the contemporary crossbred (BC) are relatively similar in the traits of growth, dam productivity and the estimate of MPPA. Key words : Composite sheep, performance of production and reproduction, intensif condition